Principles of surgical management of brain multiple metastatic abscesses - Etibarly, S. A. (Ukrainian Neurosurgical Journal, 2009)
Treatment outcomes of 56 patients with BMMA, who received surgical treatment between 1985 and 2007, are presented. MRI is the main diagnostic method that makes it possible to identify abscesses irrespective of their size, quantity and localization in the brain, as well as to differentiate them from other mass formations. In 19 patients chronic inflammation process in lungs was detected, in others — tonsillitis, osteomielitis, bacterial septicemia, in 4 cases a source of inflammation was not found or was questionable. Four methods of BMMA surgical removal were used: abscess puncturing and aspiration (in 26 patients), abscess opening and external draining (in 14 patients), abscess total excision without opening its capsule (in 7 patients), combined method — abscess puncturing or opening with its subsequent total excision (in 9 patients). The lethality rate was 19.6% (11 patients died). Deaths resulted from an irreversible cerebral dislocation disorders and heavy meningoencephalitis. Favorable outcomes of surgical intervention for BMMA are possible if simultaneous abscess sanation and evacuation from one or both cerebral hemispheres is used.